Motion verbs expressing emotion in English and their Vietnamese equivalents / Trịnh Thị Thu Hương; NHDKH Assoc.Prof.Dr Hoàng Tuyết Minh - Trịnh, Thị Thu Hương
The thesis is designed to investigate into the use of verbs of motion in emotion metaphors. The sixteen verbs studied are; climb, crawl, dive, float, fly, go, hop, jump, leap, plunge, roll, run, stagger, swim, tiptoe and walk. Verbs of motion are often used because the behavioral response to emotional impact is used as source domain for the metaphor. Climb, fly, go, hop, jump and run are used in metaphors for ANGER/FURY. Crawl, leap, run, stagger, tiptoe & walk are used in metaphors for FEAR. Float, jump, leap, roll and walk are used for JOY/HAPPINESS and go and walk are used for SADNESS. The writer uses mainly on descriptive method to describe the metaphor of the English motion verbs expressing emotion and their Vietnamese equivalents. Besides, some methods are used as the combination of qualitative and quantitative methods which contributes to this study. The results show that the connections with specific emotions seem to arise out of the semantic parameters of each verb. In this study, the majority of the studied verbs visualize a movement associated with an emotion. The study hopefully supplies some implications to language teaching, language learning as well as in translating the English motion verbs expressing emotion. The practical information is hoped to raise the language users’ awareness of the differences between the two languages.